Exploration and Processing of Pigment Source Feed Materials for Ornamental Fish Feed - Haetami, Kiki; Meidito, Agung S. (Journal of Fish Health, 2024)
Ornamental fish farming is identical to attractive colors formed from the union of genetics and digested feed sources. Exploration and processing of feed ingredients are one of the important factors added to feed formulations to increase brightness in fish. Pigment sources are divided into 2, namely natural pigment sources (plant and animal), and synthetic pigment sources as commercial materials. The application of pigment source feed ingredients is used as feed additives (nutritive and non-nutritive) which are added or mixed in the formulation. The preparation technique for adding pigment sources is carried out by spray drying, and coating (coating) in feed. Feed additives in commercial ornamental fish feed formulations can be in the form of active substances astaxanthin (C₄₀H₅₂O₄) and beta-carotene (C₄₀H₅₆) which give red-orange color, or in the form of alternative feed ingredients from spirulina, carrots, and pumpkin which give yellow and orange colors. Astaxanthin and beta-carotene dyes have been proven effective in enhancing the brightness of color in ornamental fish at a dose of 1500 ppm. The aim of the review is to provide information and insight regarding pigment source feed ingredients as well as related processing of pigment source materials using several extraction methods. The method used in this review is based on the results of a literature study using articles that have been searched on Google Scholar for the period 2012-2024. Each journal used has the results of research on pigment source materials, processing of pigment sources and their application for pigments in fish.